Avaliação da atividade antimicrobiana e anti-inflamatória do extrato glicólico de Hamamelis virginiana Linnaeus - Amendola, Isabela [UNESP] (2015)
Hamamelis virginiana L. is a North American plant that was insert in Brasil because their biological activities, like antimicrobial and anti-inflamatory activities. Large researchs are development with H. virginiana L. extracts, although there are no studies with glycolic extract from it. The objective of this work was to evaluate the antimicrobial and anti-inflammatory activity of glycolic extract of Hamamelis virginiana L. over standard strains of genus Candida yeast (C. albicans, C. dubliniensis, C. glabrata, C. guilliermondii, C. krusei e C. tropicalis), species of Gram-positive bacteria (Enterococcus faecalis, Staphylococcus aureus e Streptococcus mutans) and Gram-negative (Acinetobacter baumanii, Escherichia coli, Klebsiella pneumoniae), in plankton communities and biofilm; besides the cytotoxicity and anti-inflammatory. The antimicrobial activity was performed by microdiluition test in broth for determining the Minimum Inhibitory Concentration (MIC) e Minimum Microbicide Concentration (MMC), and the results used for antimicrobial analysis in biofilms monotypic. The cytotoxic activity was analyzed by the MTT test and quantification of production of the cytokines IL-β 1 and TNF-α by ELISA., being that the anti-inflamatory activity was performed with exposition of macrophages mouse culture to E. coli lipopolissacaride (LPS) and extract post-treatment. The results were analyzed by ANOVA and Tukey Test (p ≤ 0.05) if the results present normal distribuition; and Kruskal Wallis and post-test Dunn if the results don't presente normal distribuition (p ≤ 0.05). Results shows that the H. virginiana L. glycolic extract have antimicrobial activity about test micro-organisms and the cytotoxicity test shows high cellular viability or equal the control, except for the 100 mg/mL for 24 h contact time. Cytokines weren't produced by macrophages. Nitric oxide was produced by cells in a con...